The Impact of the Charter: Untangling the Effects of Institutional Change - Smith, Miriam (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
This article provides an overview of the main debates on the impact of the Charter's entrenchment in Canadian politics. In doing so, it casts a wide net, providing a selective exploration of the impact of the Charter in three main areas: 1) public policy; 2) political institutions and 3) political mobilization. The paper argues that we should move away from thinking about the Charter as a constitutional document that sets out rights that are protected by courts and move towards a view of the Charter as a structuring influence on Canadian political debate. In policy terms, the paper examines the instrumental impact of the Charter on criminal law and on lesbian and gay rights. While the Charter has strengthened the hand of the judiciary relative to other political institutions, the discursive and instrumental effects of the Charter are also felt in other political institutions such as the executive and Parliament as well as the operation of federalism. Perhaps most importantly, the Charter has become an important factor in structuring political mobilization and debate, encouraging civil society organizations to stake their political claims in terms of Charter rights (for better or ill) and contributing to the partisan competition between political parties in federal politics.